2022
DOI: 10.24275/rmiq/alim2963
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and non-conventional extraction of functional compounds from jiotilla (Escontria chiotilla) fruits and evaluation of their antioxidant activity

Abstract: totales del petróleo intemperizados en suelos y sedimentos (Biodegradation modeling of sludge bioreactors of total petroleum hydrocarbons weathering in soil and sediments)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…The total phenolic contents in rose vinegar were determined using the Folin-Ciocalteau colorimetric method, and the results were expressed in milligrams of gallic acid equivalent per liter (mg GAE/L) (Hasperué et al, 2016;Franco-Vásquez et al, 2023).…”
Section: Total Phenolic Contentmentioning
confidence: 99%
“…The total phenolic contents in rose vinegar were determined using the Folin-Ciocalteau colorimetric method, and the results were expressed in milligrams of gallic acid equivalent per liter (mg GAE/L) (Hasperué et al, 2016;Franco-Vásquez et al, 2023).…”
Section: Total Phenolic Contentmentioning
confidence: 99%
“…Some authors have studied the pigment content in jiotilla fruit and its microencapsulation by spraydrying. Soriano-Santos et al (2007) identified the red pigment of this fruit as betalains, which are used as natural colorants for red shades in the food industry (Bazaria and Kumar, 2017;Franco-Vásquez et al, 2023;Ravichandran et al, 2014;Stintzing et al, 2005). These authors identified that betalains from jiotilla pulp were composed of 119 ± 3.1 mg betaxanthins/kg fruit and 89 ± 6.5 mg betacyanins/kg fruit, these values represent the 19.7 ± 2.3 % of betacyanin and 41.8 ± 0.6 % of betaxanthins compared to beet, which is the only betalain-based commodity commercially used (Bazaria and Kumar, 2017;Ravichandran et al, 2014;Stintzing et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…There is an imperative need to find new or unconventional sources of food, nutrients, and micronutrients (Alpizar-Reyes et al, 2022;Franco-Vásquez et al, 2023). One of the most demanded inputs in the food industry is the use of edible oils, especially those that provide unsaturated fatty acids.…”
Section: Introductionmentioning
confidence: 99%